2021
DOI: 10.1101/2021.10.27.466190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A decade of stability for wMel Wolbachia in natural Aedes aegypti populations

Abstract: Mosquitoes carrying Wolbachia endosymbionts are being released in many countries for arbovirus control. The wMel strain of Wolbachia blocks Aedes-borne virus transmission and can spread throughout mosquito populations by inducing cytoplasmic incompatibility. Aedes aegypti mosquitoes carrying wMel were first released into the field in Cairns, Australia, over a decade ago, and with wider releases have resulted in the near elimination of local dengue transmission. The long-term stability of Wolbachia effects is c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 57 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Here we used a combination of repeated field collections, antibiotic curing and reciprocal backcrossing to show that fitness costs depend on genetic background and shift with laboratory adaptation. This finding is consistent with previous studies demonstrating the potential for host genetic changes to mediate fitness costs [15,41] and the lack of changes in the wMel genome itself [21][22][23]. We have previously found that the genomes of Ae.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Here we used a combination of repeated field collections, antibiotic curing and reciprocal backcrossing to show that fitness costs depend on genetic background and shift with laboratory adaptation. This finding is consistent with previous studies demonstrating the potential for host genetic changes to mediate fitness costs [15,41] and the lack of changes in the wMel genome itself [21][22][23]. We have previously found that the genomes of Ae.…”
Section: Discussionsupporting
confidence: 93%
“…In Cairns, Australia, post-release monitoring found persistent costs of the wMel infection to female fertility [26] and sustained virus blocking [40] after one year. Phenotypic effects have largely persisted in the longer term, with one exception being development time where costs were only apparent in a laboratory background [23]. However, no studies to date have identified the basis of population differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations